2010
DOI: 10.1002/jcp.22255
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid receptor 1 mediates palmitic acid‐induced apoptosis via endoplasmic reticulum stress in human renal proximal tubular cells

Abstract: The endocannabinoid system (ECS) is activated at the onset of obesity and diverse metabolic diseases. Endocannabinoids mediate their physiological and behavioral effects by activating specific cannabinoid receptors, mainly cannabinoid receptor 1 (CB(1)R). Diabetic nephropathy (DN) is induced by hyperlipidemia, and renal proximal tubule cells are an important site for the onset of DN. However, the pathophysiology of CB(1)R, especially in the hyperlipidemia of DN, has not been elucidated. Therefore, we examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 104 publications
5
50
1
2
Order By: Relevance
“…In addition, the hippocampal densities of CB 1 R protein and specific CB 1 R binding sites are significantly increased in the animal model of streptozotocin-induced type 1 diabetes (13). Our recent report also demonstrated that palmitic acid induces CB 1 R activation in proximal tubule cells, suggesting that hyperlipidemia increases CB 1 R activation, which may be associated with the onset of diabetic nephropathy (28). Nonetheless, the involvement of CB 1 R activation in the hyperglycemia-induced onset of diabetic nephropathy was not evidenced.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In addition, the hippocampal densities of CB 1 R protein and specific CB 1 R binding sites are significantly increased in the animal model of streptozotocin-induced type 1 diabetes (13). Our recent report also demonstrated that palmitic acid induces CB 1 R activation in proximal tubule cells, suggesting that hyperlipidemia increases CB 1 R activation, which may be associated with the onset of diabetic nephropathy (28). Nonetheless, the involvement of CB 1 R activation in the hyperglycemia-induced onset of diabetic nephropathy was not evidenced.…”
Section: Discussionmentioning
confidence: 70%
“…This procedure was performed as our previous study (28). The primers used were 5=-cttcactcctgaaggggagc-3=(sense), 5=-ccttctttcccaaatacgcc-3=(antisense) for GRP78: denaturation at 94°C for 5 min and 30 cycles at 94°C for 30 s, 62°C for 1 min and 68°C for 2 min, followed by a 7-min extension at 68°C.…”
Section: Methodsmentioning
confidence: 99%
“…In a rat model of type 2 diabetes nephropathy, in vivo treatment for 3 months with a CB1 antagonist in the prediabetic stage prevents nephropathy, or reverses it when this is already developed (410). Palmitic acid, a player in renal tubular damage, upregulates CB1 mRNA and protein expression and promotes receptor internalization, and, by activating endoplasmic reticulum stress, induces intrinsic pathway apoptosis via CB1 (480). Higher CB1 expression and internalization are also reported in primary rat mesangial cells exposed to high glucose (481), and CB1 is among the most upregulated genes in mice subjected to unilateral ureteral obstruction, an experimental model of renal fibrosis.…”
Section: Kidneymentioning
confidence: 99%
“…Several recent reports (Table 1) have documented the presence of functional CB 1 receptor in the entire kidney [15,[33][34][35][36][37][38][40][41][42], including different parts of the nephron such as afferent and efferent arterioles [39], glomeruli [33,38,40,42,43], tubules [15], the loop of Henle [44], and collecting ducts [15]. It is also expressed in various subtypes of kidney cells such as podocytes [33,41,43,45,46], proximal and distal tubular epithelial cells [15,34,37,38,40,41,[47][48][49], and mesangial cells [50,54]. Moreover, CB 1 receptors are expressed in human clear-and chromophobe-renal cell carcinomas, as well as in renal oncocytoma [55,56].…”
Section: The Renal Ecb Systemmentioning
confidence: 99%
“…In fact, PA upregulates CB 1 receptor mRNA and protein expressions and promotes the receptors internalization in these cells. Furthermore, PA-induced activation of CB 1 receptor decreases cell proliferation and induces apoptosis by inducing the ER stress response, effects that are completely antagonized by either pharmacological blockade of CB 1 receptor or siRNA knockdown [47].…”
Section: Role Of Cb 1 Receptors In Dnmentioning
confidence: 99%